Indian food: A Historical companion - Achaya, K. T. (New Delhi Oxford University Press, 1998)
Outside India Indian food is popular the world over, from Tokyo to Telford and from Canberra to California. For centuries India has produced an unusually diverse cuisine. The food of the 17 states that make up India is as varied as the food of the countries of Europe. It was in India that the Aryan cultural ethos flowered, bringing to every area of human activity, including food and dietetics, a spiritual and moral dimension.